The Role of culture in media architecture under Flow Theory - Li, Gengrui; Sodbhiban, Pichai (Saengtham College Journal, 2025)
Media architecture is an emerging art situation that combines digital media with urban building facades. This paper discusses the role of cultural, technological and aesthetic elements in the development of digital media in architectural art. Based on a review of relevant literature and empirical data collected through investigation, this paper explores the influence of cultural, technical and aesthetic factors on the design, implementation and visitor acceptance of media architectural projects by using qualitative methods of word frequency analysis through tourist interviews and expert interviews. The study found that cultural values, traditions and aesthetics play a key role in shaping media architecture in terms of visitor perception and psychological experience. In particular, the impact of the digital media components of architectural art on visitor satisfaction under the mediating influence of flow theory, the paper concludes by discussing the implications of these findings for future research and practice in the field of media architecture, highlighting the need for a more nuanced and culturally sensitive approach to the design and implementation of media architecture projects.